Do hip-abduction braces work?—A biomechanical evaluation of a commercially available hip brace - Michalik, Roman; Essing, Katrin; Rohof, Ben; Gatz, Matthias; Migliorini, Filippo; Betsch, Marcel (Archives of Orthopaedic and Trauma Surgery, 2022)
Introduction: Dislocations of the hip joint are a common and clinically relevant complication following total hip arthroplasty (THA). Hip-abduction braces are currently used following operative or non-operative treatment of THA dislocations to prevent re-dislocations. However, the clinical and biomechanical effectiveness of such braces is still controversial. Material and methods: A total of 30 volunteers were measured during standing and during sitting up and down from a chair task wearing a hip brace set at 70°, 90° or no hip flexion limitation. Range of motion of the hip joint was measured in all directions by an inertial sensor system. Further it has been evaluated if the range of motion would be reduced by the additional use of an arthrodesis cushion. Results: The use of a hip brace set up with flexion limitation did reduce hip ROM in all directions significantly compared to unhinged brace (p < 0.001–0.035). Performing the “sit down and stand-up task” the brace set up at 70° flexion limitation did reduce maximum hip flexion significantly (p = 0.008). However, in most cases the measured hip flexion angles were greater than the settings of the hip brace should have allowed. The additional use of a cushion can further limit hip motion while sitting up and down from a chair. Conclusion: This study has demonstrated that hip-abduction braces reduce hip range of motion. However, we also found that to achieve a flexion limitation of the hip to 90°, the hip brace should be set at a 70° hip flexion limitation.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Arthrodesis cushion; Hip brace; Hip dislocation; Inertial sensors; Total hip arthroplasty